2010
DOI: 10.1093/aob/mcq079
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of tillering in sorghum: environmental effects

Abstract: This result was consistent with the hypothesis that internal plant competition for assimilates regulates tillering in sorghum. Hence, the framework outlined has a predictive value that could provide the basis for dynamic simulation of tillering in crop growth models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 49 publications
8
96
0
1
Order By: Relevance
“…However, significant genotype  season interactions, especially between earlier (October 2011-12) and later plantings (November 2010-11 and2012-13), indicated that variability in photoperiod or temperature sensitivity could have affected canopy development (e.g. Bos and Neuteboom 1998;Kim et al 2010aKim et al , 2010bvan Oosterom et al 2011). Leaf expansion is also known to be sensitive to VPD (e.g.…”
Section: Observed Variability In Traits Affecting Plant Water Usementioning
confidence: 99%
“…However, significant genotype  season interactions, especially between earlier (October 2011-12) and later plantings (November 2010-11 and2012-13), indicated that variability in photoperiod or temperature sensitivity could have affected canopy development (e.g. Bos and Neuteboom 1998;Kim et al 2010aKim et al , 2010bvan Oosterom et al 2011). Leaf expansion is also known to be sensitive to VPD (e.g.…”
Section: Observed Variability In Traits Affecting Plant Water Usementioning
confidence: 99%
“…The final area of main shoot leaves 5 and 9 was obtained for the same plants from their final length and maximum width, multiplied by a shape factor of 0.69 (Kim et al 2010b). A generic measure of the increase in size of successive leaves between leaves 5 and 9 was obtained as the leaf length increase rate ) and leaf width increase rate ).…”
Section: Phenotypic Trait Measurementmentioning
confidence: 99%
“…Similar increased vigour during early growth, evident in greater leaf appearance rate, has also been associated with a decrease in tiller number in ATx642, which is the donor parent of the Stg1-4 introgressions, compared to AQL39, a senescent hybrid (van Oosterom et al, 2011). It is thought that competition for carbon between early leaves and tillers lead to this suppression in tillering in genotypes with greater LAR or increased size of early leaves (Alam et al, 2014;Kim et al, 2010). In accordance with this, reducing carbon supply by removing leaves (and therefore photo-assimilate) also led to a reduction in tillering (Kebrom and Mullet, 2015).…”
Section: Discussionmentioning
confidence: 90%